2020
DOI: 10.1186/s41239-020-00219-w
|View full text |Cite
|
Sign up to set email alerts
|

Recommender systems to support learners’ Agency in a Learning Context: a systematic review

Abstract: Recommender systems for technology-enhanced learning are examined in relation to learners’ agency, that is, their ability to define and pursue learning goals. These systems make it easier for learners to access resources, including peers with whom to learn and experts from whom to learn. In this systematic review of the literature, we apply an Evidence for Policy and Practice Information (EPPI) approach to examine the context in which recommenders are used, the manners in which they are evaluated and the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…Without compromising the generality, we assume that the values of these QoEs are sorted in a truly ascending order, that is, Q A < Q B < Q C , which indicates that the higher the recommendation identifier ( A , B , C ), the better the recommendation. A simple and effective metric that allows QoE verification for each user is the relative visit time ratio, which we define as [ 17 , 18 ] where the denominator is the total time that other users devote to their visit simultaneously as i . So we can easily observe that when the sum of the times of other users increases, then either the risk becomes higher, or the same number of users spend total time on the visit, which gives us an indication of the risk of misuse of the platform.…”
Section: Proposed Approachmentioning
confidence: 99%
“…Without compromising the generality, we assume that the values of these QoEs are sorted in a truly ascending order, that is, Q A < Q B < Q C , which indicates that the higher the recommendation identifier ( A , B , C ), the better the recommendation. A simple and effective metric that allows QoE verification for each user is the relative visit time ratio, which we define as [ 17 , 18 ] where the denominator is the total time that other users devote to their visit simultaneously as i . So we can easily observe that when the sum of the times of other users increases, then either the risk becomes higher, or the same number of users spend total time on the visit, which gives us an indication of the risk of misuse of the platform.…”
Section: Proposed Approachmentioning
confidence: 99%
“…The phases suggested by [16] were taken as reference in order to conduct the systematic review of literature (SRL), and these are shown in the following diagram (Figure 1). education, target users are students, teachers, and academic advisors, and the recommended elements are educational materials, learning objects, papers, universities, and information such as that about courses, student performance, and the field of study [11].…”
Section: Methodsmentioning
confidence: 99%
“…The total score will have a value between 0 and 16, classifying them as deficient (0-2), sufficient (3)(4)(5), good (6-10), very good (11)(12)(13), and excellent (14-16).…”
Section: Metrics Value Weightmentioning
confidence: 99%
“…Moreover, we only focused on a specific topic that investigates the impact of exploiting SEGs in formal education as well as the role of LA in improving the usability of such environments. Hence, future research can explore other issues and research challenges not addressed by the studies included in this review like the design of interactive LA dashboards and recommender systems in education (Deschênes, 2020 ).…”
Section: Conclusion and Limitationsmentioning
confidence: 99%